Asia-Pacific trade and investment report., 2009,. (United Nations Economic and Social Commission for Asia and the Pacific, 2009)
Provides an in-depth analysis of recent trends and developments in trade and investment in the region just before and during the current crisis and seeks to explore issues related to the formulation of inclusive and sustainable trade. The report calls for a rebalancing of the roles of business and government in trade and trade policy formulation.